A study on the Importance of Communication Management in an Organisation - Yashwant Patel (AG Volumes, 2022)
When it comes to making decisions and developing plans, communication is really necessary. It makes it feasible for management to protect information, the absence of which would prevent them from making any decisions at all. The efficacy of management judgment is directly proportional to the clarity of interpersonal communication. In addition, it is necessary for the choices and plans made by management to be conveyed to those who are under supervision. It is likely that giving directions to other people will be impossible if efficient communication cannot take place. The management’s goals and strategies may be more successfully carried out with the assistance of effective communication. The goal of management is to get things done via other people, and this goal cannot be achieved unless there is cohesion of purpose and harmony of effort. Management may be seen of as the practice of influencing others to carry out one’s plans. Communication, which includes the sharing of thoughts and information, is one of the most effective ways to foster unity of action in the service of a shared goal. It serves to link the people together and makes it easier for them to coordinate. Efficiency in management may be increased by effective communication. It is a well-known fact that in management, nothing will take place unless and until communication is established. The capacity of a manager to communicate clearly and effectively with the people that make up the organisation he oversees is directly proportional to that manager’s level of productivity. The only way for management to transmit its aims and ambitions, give instructions and orders, distribute positions and responsibility, and assess the performance of subordinates is via communication.